Acesso aos níveis de atenção à saúde em um município do Estado de São Paulo: perspectivas de gestores, profissionais e usuários - Nardo, Luciana Rocha de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The purpose of this study was to understand the user access to the reference services, the perspective of view of managers, healthcare professionals and users of the brazilian Unique Health System (SUS). It was chosen to use the qualitative approach, in the aspect of Alfred Schütz Social Phenomenology. By means of contextualized statements of experiences it was possible to unveil the reasons why and the reasons for of the research subjects regarding the access to more complex attention levels. This research included 32 participants: 15 healthcare professionals, nine managers and eight users. All interviews were recorded and generated three concrete categories that follow highlighted with its respective central ideas: 1) Suppressed demand in medical specialties and complementary exams - lack of investments in public health sector, lack of infrastructure of the health services, poor professional training and qualification, poor customer service, health care centered on a fragmented and biological model, difficulties in the organization and management of health services and demand greater than supply. 2) Facilities in the access to healthcare actions - the importance of SUS, social control and integrality of actions, good qualification and service of the professionals and managers involved in health care, availability of resources in the municipality itself, Family Health Strategy to contribute to access, humanization of care and disease prevention and 3) Achieve improved access to medical specialties and complementary exams - investment in healthcare and control of resources by the public service, implementation of specialized medical services, integrated communication systems and joint efforts for the development and use of protocols as a tool for health system organization, prioritization of specialties and exams according to the severity and humanization of health care. Therefore, Alfred Schütz Social Phenomenology allowed a ...

O objetivo deste estudo foi compreender o acesso do usuário aos serviços de referência, a partir da perspectiva de gestores, profissionais de saúde e usuários do Sistema Único de Saúde (SUS). Optou-se pela abordagem qualitativa, na vertente da Fenomenologia Social de Alfred Schütz. Por meio dos depoimentos das vivências contextualizadas foi possível desvelar os motivos porque e os motivos para dos sujeitos da pesquisa sobre o acesso aos níveis de atenção de maior densidade tecnológica. Esta pesquisa contou com 32 participantes, sendo 15 profissionais da saúde, nove gestores e oito usuários. As entrevistas foram audiogravadas e emergiram três categorias concretas do vivido que seguem em destaque com suas respectivas idéias centrais: 1) Demanda Reprimida nas especialidades médicas e exames complementares - falta de investimento no setor público de saúde, falta de infraestrutura dos serviços de saúde, má formação e qualificação profissional, mau atendimento, atenção à saúde centrada no modelo fragmentado e biológico, dificuldades na organização e gestão dos serviços de saúde e demanda maior que a oferta. 2) Facilidades no acesso às ações de saúde - importância do SUS, controle social e integralidade das ações, qualificação e bom atendimento dos profissionais e gestores envolvidos na atenção à saúde, disponibilidade de recursos no próprio município, Estratégia Saúde da Família na contribuição do acesso, humanização do cuidado e prevenção de doenças e 3) Alcançar a melhoria do acesso às especialidades médicas e exames complementares - investimento na área da saúde e controle dos recursos pelo serviço público, implantação de serviços médicos especializados, sistemas integrados de comunicação e mutirões, desenvolvimento e utilização de protocolos como instrumento para organização do sistema de saúde, priorização de...
Access to healthcare levels in a city the State of São Paulo: perspectives of managers, professionals and users
Keywords: Cuidados primários de saúde; Saúde pública; Administradores de saude; Cuidados médicos - Avaliação; Acesso aos serviços de saúde; Sistema Único de Saúde (Brasil); Health services accessibility